Servical Dilatation Measuring Device - Putri, Winda Astria; Widyawati, Melyana Nurul; Kurnianingsih, Kurnianingsih (GLOBAL HEALTH SCIENCE GROUP, 2024)
Childbirth represents a physiological phenomenon encountered by females subsequent to the gestational process, necessitating the assistance of healthcare professionals for its monitoring also evaluation. Presently, the manual assessment of cervical dilation through digital palpation by obstetricians or midwives remains the prevailing approach. Nonetheless, manual cervical manipulation is administered by healthcare providers in various clinical settings, leading to subjective also potentially imprecise diagnostic results, which heavily depend on the skill also clinical judgment of the provider. This study aims to examine the development of cervical dilation measurement tools from 1998 to 2015. It underscores the imperative for a tool capable of delivering impartial also precise assessments devoid of human influence. This inquiry adopts a literature review methodology, employing Evidence Based Practice (EBP) as the framework for exploration, leveraging Google Scholar as the primary database. The retrieved literature, spanning from 1995 to 2005, exclusively comprises international journals. Within this systematic scrutiny, apparatuses utilized for dilation measurement are systematically cataloged as per their operational principles also clinical utility. The analysis suggests that image data processing technology holds considerable promise for refinement into instrumentation dedicated to cervical dilation assessment.